Synthesis of solar-activated materials for the controlled release of volatile compounds - Oliveira, L. Filipa (2012)
This work envisages the study of photocatalytic thin films deposited by physical vapor deposition, with functional properties that allows the controlled release of volatile agents (e.g., insecticides, repellents, deodorants, fragrances, etc.), from the interior of polymeric micro capsules, after activation by sunlight, or similar light. As an ultimate goal, a quantification of the inherent controlled release of a particular volatile agent is determined by gas chromatography coupled with mass spectroscopy, in order to standardize the tests, so that an application can be offered to a wide range of supports from various industrial sectors, such as in textiles (clothing/curtains), packaging (deodorizers/air fresheners), glass (self-cleaning windows with controlled release of insecticide/repellent/air freshener/deodorant), plastics (automotive), amongst others. This technology takes advantage of the established photocatalytic property of titanium dioxide for the use as an active surface/site to promote the controlled release of a specific vapor (volatile agent) from within the aforementioned capsules.